THE EFFECTIVENESS OF JIGSAW TECHNIQUE IN IMPROVING STUDENTS' READING COMPREHENSION - Kwania, Yuli (2016)
This research investigated the senior high school students' reading comprehension improvement by implementing Jigsaw technique in exposition text. The design of this study is quasi experimental design which used treatment group and control group. Both treatment group and control group consist of 34 eleventh grade students of senior high school. The instruments that are employed in this study are pre-test, post-test and questionnaire. The findings from pre-test and post-test are analyzed by t-test. Based on this research, the implementation of Jigsaw technique is efective in improving students' reading comprehension. The mean of normalized gain in treatment group is 0.59 and the mean of normalized gain in control group is 0.36. The result of this study showed that Jigsaw technique is effective in improving students reading comprehension and the result of students' responses toward Jigsaw technique is excellent. Keywords: Jigsaw technique, reading comprehension, exposition text.